KAJIAN ARSITEKTUR HIJAU DALAM PENGEMBANGAN DESAIN GEDUNG PEMERINTAHAN - Zahmi Afrizal (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2017)
Title: Green Architecture Study in The Development of Government Building Designs The development of constructing the building especially the government building develop rapidly and increasing the number of needs in each region or province in Indonesia. Issues concerning environmental problems resulting from the impact of the development of government buildings in Indonesia at this time such as environmental degradation, global warming, energy and water crises into the background of the emergence of the concept of green architecture or environmentally friendly architecture. The components of green architecture within the building and its environment relate to the site management, energy efficiency, water use efficiency, indoor air quality, environmentally friendly materials, waste management, wastewater management, and vegetation placement are necessary to be researched. The results of this study is expected to be a reference and design guidelines on the development of government buildings in Indonesia to become green buildings that are environmentally friendly.